A thiopyrylium salt for PET/NIR‐II tumor imaging and image‐guided surgery. Issue 5 (7th April 2020) - Zhang, Xiao; Ding, Bingbing; Qu, Chunrong; Li, Huiling; Sun, Yu; Gai, Yongkang; Chen, Hao; Fang, Hanyi; Qian, Kun; Zhang, Yongxue; Cheng, Zhen; Lan, Xiaoli
Abstract : All tumor imaging modalities have resolution limits below which deeply situated small metastatic foci may not be identified. Moreover, incomplete lesion excision will affect the outcomes of the patients. Scintigraphy is adept in locating lesions, and second near‐infrared window (NIR‐II) imaging may allow precise real‐time tumor delineation. To achieve complete excision of all lesions, multimodality imaging is a promising method for tumor identification and management. Here, a NIR‐II thiopyrylium salt, XB1034, was first synthesized and bound to cetuximab and trans‐cyclooctene (TCO) to produce XB1034‐cetuximab‐TCO. This probe provides excellent sensitivity and high temporal resolution NIR‐II imaging in mice bearing tumors developed from human breast cancer cells MDA‐MB‐231. To enable PET imaging, 68 Ga‐NETA‐tetrazine is subsequently injected into the mice to undergo a bio‐orthogonal reaction with the preinjected XB1034‐cetuximab‐TCO. PET images achieved in the tumor models using the pretargeting strategy are of much higher quality than those obtained using the direct radiolabeling method. Moreover, real‐time NIR‐II imaging allows accurate tumor excision and sentinel lymph node mapping. In conclusion, XB1034 is a promising molecular imaging probe for tumor diagnosis and treatment. Abstract : Here, a NIR‐II thiopyrylium salt, XB1034, was first synthesized and bound to cetuximab and trans‐cyclooctene (TCO) to produce XB1034‐cetuximab‐TCO. XB1034‐cetuximab‐TCO manifested promising NIR‐II imaging activity, and the follow‐up injected Tz‐NETA‐ 68 Ga probe showed encouraging efficiency for tumor quantification. This targeted dual‐modality probe demonstrated the feasibility of clinical image‐guided operation in real time.